Individualism-collectivism, attributions and leadership styles of Asian and Western managers - Mayoralgo-Nolasco, Jocelyn M. (2005)
The study examined differences on individualism-collectivism, attributions for work performance and leadership style of Asian and Western managers. Fifty Asian and forty managers from five multinational companies participated in the study. Consistent with expectation, Asian managers scored significantly higher in collectivism. Western managers, on the other hand, scored significantly higher in individualism. Based on the four causal factors delineated by Weiner, Frieze, Kukla, Reed, Rest, and Rosenbaum's (1972) model of attribution for task performance, both groups of managers attributed good work performance more to ability and effort and poor performance was attributed to task difficulty. However, Asian managers more than their Western counterparts perceived that luck contributed to work performance. They also believed other situational factors were important causes of work performance. In terms of leadership style, results indicated that both groups of managers have the same leadership style. Implications for future leadership research and for organizations seeking to manage diversity were discussed.
Includes bibliographical references (pages 71-74).